Mechanisms of melanocyte polarity and differentiation: What can we learn from other neuroectoderm-derived lineages?. (December 2020) - Li, Mengnan; Knapp, Sina K.; Iden, Sandra
Abstract: Melanocytes are neuroectoderm-derived pigment-producing cells with highly polarized dendritic morphology. They protect the skin against ultraviolet radiation by providing melanin to neighbouring keratinocytes. However, the mechanisms underlying melanocyte polarization and its relevance for diseases remain mostly elusive. Numerous studies have instead revealed roles for polarity regulators in other neuroectoderm-derived lineages including different neuronal cell types. Considering the shared ontogeny and morphological similarities, these lineages may be used as reference models for the exploration of melanocyte polarity, for example, regarding dendrite formation, spine morphogenesis and polarized organelle transport. In this review, we summarize and compare the latest progress in understanding polarity regulation in neuronal cells and melanocytes and project key open questions for future work. Graphical abstract: Shared and distinct polarity features in neurons and melanocytes. Melanocytes share some morphological or molecular similarities with neuronal cells in terms of dendrite formation, spine formation, and directional organelle transport, whereas other characteristics are distinct for neurons and melanocytes, respectively. KC, keratinocyte; MC, melanocyte; UV, ultraviolet. Image 1